The Effect of Ethyl Methane Sulfonate (EMS) on The In Vitro Shoot Regeneration of Vetiver (Vetiveria zizanioides [L.] Nash) - Widoretno, Wahyu; Indriyani, Serafinah (The Journal of Experimental Life Science, 2020)
Production of vetiver in Indonesia is low, and its oil quality is not in line with market demand due to the low quality of plant raw materials. In vitro mutagenesis using ethyl methanesulfonate (EMS) has the potential to produce superior vetiver variants. This study aimed to determine the effect of EMS on the growth and shoot formation of in vitro vetiver plants. In vitro mutagenesis was performed by culturing in vitro shoots on MS medium containing EMS with various concentrations (0.02; 0.04; 0.06; 0.08; 0.1%) for 4 weeks. The results showed that the addition of 0.02-0.1% EMS to the medium affected on in vitro shoot growth and the ability to form new shoots. EMS increased the percentage of dead explants and decreased the average number of shoots, the number of shoots formed per explant, and the shoot fresh weight. The higher the EMS concentration in the medium, the smaller the percentage of survived explants and the lower ability to form new shoots with the average number of shoots formed less. The percentage of survived explants on the medium without the addition of EMS and on the medium with the addition of EMS with low concentrations of 0.02 and 0.04% reached 100% with an average number of shoots formed ranging from 8.5-10 shoots/explant. Meanwhile, the percentage of survived explants on medium with the addition of EMS with a high concentration of 0.08-0.1% was only 12.5-25% with an average number of shoots formed was less than 2 shoots/explant.Keywords: EMS, in vitro shoots, Vetiveria zizanioides.